Decentralised Energy (Ubiquity Press, 2021)
As the contribution of renewable energy increases to meet climate change objectives, so does the extent to which electricity is generated by individuals and communities, moving a centralised system to a more decentralised one, with associated system management and integration challenges. However, new digital and storage technologies are enabling local system management, and reducing the need for, and cost of, centralised planning.